2015
DOI: 10.1007/s10009-015-0402-1
|View full text |Cite
|
Sign up to set email alerts
|

Model checking of state-rich formalism by linking to $$CSP\,\Vert \,B$$ C S P ‖ B

Abstract: Since state-rich formalism Circus is a combination of Z, CSP, refinement calculus and Dijkstra's guarded commands, its model checking is intrinsically more complicated and difficult than that of individual state-based languages or process algebras. Current solutions translate executable constructs of Circus programs to Java with JCSP, or translate them to CSP processes. Data aspects of Circus programs are expressed in the Java programming language or as CSP processes. Both of them have disadvantages. This work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, with Circus2CSP, we were able to go beyond the range 0 up to 90 in less than a minute. Such a result demonstrated that our approach is capable of handling large-scale case studies like the haemodialysis machine [12] and the ring buffer [38,26].…”
Section: Experiments With Circus2cspmentioning
confidence: 92%
See 1 more Smart Citation
“…However, with Circus2CSP, we were able to go beyond the range 0 up to 90 in less than a minute. Such a result demonstrated that our approach is capable of handling large-scale case studies like the haemodialysis machine [12] and the ring buffer [38,26].…”
Section: Experiments With Circus2cspmentioning
confidence: 92%
“…Finally, we compare different approaches for modeling the Ring Buffer case study [26,38], using FDR, in order to test the capabilities of our tool while modelchecking the translated models, in contrast to the limitations of ProB [19]. Unfortunately, the structure defined for our translation strategy is not fully supported by ProB, which was used to test the model generated with the translation strategy from Ye [38]. ProB is another model-checker, which was originally developed for the B language, and was extended to support CSP, Z, Event-B [1], as well as combined languages such as CSP||B.…”
Section: Experiments With Circus2cspmentioning
confidence: 99%
“…Apart from CSP and TA, model transformations have been used for improving various formal modelling notations. For instance, Circus has been translated into CSP||B for using the tool ProB for automatic verification [36]. Additionally, the language B has been translated into TLA+ for automatic validation with TLC [18].…”
Section: Related Workmentioning
confidence: 99%
“…CSP has also been a popular target for domain specific formalisms such as Casper [54] for security protocols or Circus [74]. For the latter there is also a recent translation to CSP B [75], and Circus itself is sometimes the target for other formalisms such as UML [16].…”
Section: Other High-level Languagesmentioning
confidence: 99%